2005
DOI: 10.1016/j.jtcvs.2004.09.014
|View full text |Cite
|
Sign up to set email alerts
|

The effects of steroids on the occurrence of postoperative atrial fibrillation after coronary artery bypass grafting surgery: A prospective randomized trial

Abstract: Prophylactic short-term steroid administration in patients undergoing coronary artery bypass grafting significantly reduced postoperative atrial fibrillation. In this study, there was no significant difference between the steroid group and the placebo group with regard to the length of hospital stay; however, the steroid group had more complications, which may contribute to prolonged hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(56 citation statements)
references
References 30 publications
3
53
0
Order By: Relevance
“…This approach has already been tried with success in other surgical fields, notably in cardiac surgery [70,71]. The administration of steroids in patients post coronary artery bypass grafting has been associated with improved patient outcomes (significant reduction in postoperative atrial fibrillation) [71].…”
Section: Postoperative Biological Markers As Predictors Of Post-op Painmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach has already been tried with success in other surgical fields, notably in cardiac surgery [70,71]. The administration of steroids in patients post coronary artery bypass grafting has been associated with improved patient outcomes (significant reduction in postoperative atrial fibrillation) [71].…”
Section: Postoperative Biological Markers As Predictors Of Post-op Painmentioning
confidence: 99%
“…This approach has already been tried with success in other surgical fields, notably in cardiac surgery [70,71]. The administration of steroids in patients post coronary artery bypass grafting has been associated with improved patient outcomes (significant reduction in postoperative atrial fibrillation) [71]. A randomized clinical trial involving 34 patients undergoing bilateral TKA revealed that the administration of three doses of intravenous hydrocortisone (100 mg per dose) significantly decreased the degree of inflammation as measured by serum IL-6 level at 24 h after surgery compared to the placebo group.…”
Section: Postoperative Biological Markers As Predictors Of Post-op Painmentioning
confidence: 99%
“…Corticosteroids were evaluated as part of a regimen including beta blockers to prevent AF in 2 studies. 9,10 One randomized, double-blinded, multicenter study of 241 cardiac surgery patients evaluated a low dose of hydrocortisone (100 mg following surgery, then 100 mg every 8 hours for 3 days). 9 Although a power analysis was not described, the incidence of new onset AF during the fi rst 84 hours after cardiac surgery was 48% in the placebo group compared to 30% in the hydrocortisone group (hazard ratio, 0.54; 95% CI, 0.36-0.82; P = .01).…”
Section: Atrial Fibrillationmentioning
confidence: 99%
“…These results were consistent with a smaller but similar study, also using low dosing of corticosteroids (1,000 mg hydrocortisone prior to CPB followed by dexamethasone 4 mg every 6 hours for 1 day postoperatively). 10 Two meta-analyses evaluated the dose-dependent effect of corticosteroids on postoperative AF. 6,11 To avoid signifi cant heterogeneity, Marik and colleagues excluded studies using doses less than 200 mg/day and more than 10,000 mg/day of hydrocortisone equivalents.…”
Section: Atrial Fibrillationmentioning
confidence: 99%
“…[75][76][77][78] Reasons that corticosteroids may be effective for prevention of post-CABG AF but associated with induction of AF in patients not undergoing surgery are unclear. Evidence indicates that AF may occur in part as a result of an inflammatory process; inflammation may be particularly important as a mechanism of postoperative AF, and corticosteroids may reduce the risk of post-CABG AF due to antiinflammatory properties.…”
Section: Corticosteroids (Quality Of Evidence -Low)mentioning
confidence: 99%